The SIAH2-NRF1 axis spatially regulates tumor microenvironment remodeling for tumor progression - Ma, Biao; Cheng, Hongcheng; Mu, Chenglong; Geng, Guangfeng; Zhao, Tian; Luo, Qian; Ma, Kaili; Chang, Rui; Liu, Qiangqiang; Gao, Ruize; Nie, Junli; Xie, Jiaying; et al. (Nature communications, 2019)
The interactions between tumor cells with their microenvironments, including hypoxia, acidosis and immune cells, lead to the tumor heterogeneity which promotes tumor progression. Here, we show that SIAH2-NRF1 axis remodels tumor microenvironment through regulating tumor mitochondrial function, tumor-associated macrophages (TAMs) polarization and cell death for tumor maintenance and progression. Mechanistically, low mitochondrial gene expression in breast cancers is associated with a poor clinical outcome. The hypoxia-activated E3 ligase SIAH2 spatially downregulates nuclear-encoded mitochondrial gene expression including pyruvate dehydrogenase beta via degrading NRF1 (Nuclear Respiratory Factor 1) through ubiquitination on lysine 230, resulting in enhanced Warburg effect, metabolic reprogramming and pro-tumor immune response. Dampening NRF1 degradation under hypoxia not only impairs the polarization of TAMs, but also promotes tumor cells to become more susceptible to apoptosis in a FADD-dependent fashion, resulting in secondary necrosis due to the impairment of efferocytosis. These data represent that inhibition of NRF1 degradation is a potential therapeutic strategy against cancer. Tumor cell-microenvironment interactions generate heterogeneity and promote progression. Here, Ma et al. show that the E3 ligase SIAH2 degrades NRF1 in response to hypoxia to enhance pro-tumor metabolic and environmental effects, whereas NRF1 stabilization sensitizes tumor cells to apoptosis.